Behaviour of Tritium and Tritiogenic Helium in Freshwater Lens Groundwater Systems: Insights from Langeoog Island, Germany. (7th October 2019) - Post, Vincent E. A.; Houben, Georg J.; Stoeckl, Leonard; Sültenfuß, Jürgen
Abstract : Tritium ( 3 H) and its daughter product 3 He have been widely used as tracers in hydrological studies, but quantitative analyses of their behaviour in freshwater lenses and the transition zone in coastal aquifers are presently lacking. In this paper, the fate of 3 H and 3 He in the freshwater lens and the transition zone as well as the saltwater wedge is studied using numerical variable-density flow and transport models of different degrees of complexity. The models are based on the conditions on the German island of Langeoog, which is uniquely suited for this purpose because of the high 3 H concentration of the North Sea. It is found that most bomb-related tritiogenic 3 He still resides in the freshwater lens, making it a useful tracer for young (<60 years) groundwater. Differences in dispersive transport between 3 H and 3 He can cause an apparent age bias on the order of 10 years. Under favourable conditions, 3 H from seawater can penetrate deep into the offshore part of the aquifer and has potential to be used as a tracer to study saltwater circulation patterns. Our modelling suggests that the field-observed 3 H in the transition zone does not originate from seawater but from freshwater affected by the bomb peak. Yet in models with a low (α L = 0.5   m ) dispersivity, no 3 H was sequestered into the transition zone and the transition zone width was underestimated. Better results were obtained withα L = 5   m, a value that is higher than in comparable modelling studies, which suggests that further work is needed to better understand the controls (tides, lithological heterogeneity, or transience of recharge and pumping) on transition zone mixing processes.